2006
DOI: 10.1557/proc-0916-dd04-10
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Carrier Dynamics and Recombination in Green Emitting InGaN MQW LED

Abstract: Ultrafast spectroscopy, in particular time-resolved photoluminescence, can help in the development of InGaN/GaN heterostructures for long wavelength visible emitters. In this paper, we present recent results that underscore the current understanding of two approches to achieve desired emission characteristics and recombination mechanisms in InGaN/GaN MQWs for green LEDs. Specifically, the photoluminescence decay of samples grown using two different design approaches is discussed. In one approach, samples, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…The comparison of photoluminescence of the GaN layers deposited on the Al face and on the N face of the single-crystal AlN substrate showed that in the former case photoluminescence is consistent with that of the homoepitaxial Ga-face GaN while in the latter an existance of the tail localized states was found (Tamulatis et al, 2003). The studies of deep-UV emission of AlGaN quantum wells (Gaska et al, 2002) as well as AlGaN UV (Nishida et al, 2004a;Ren et al, 2007;Xi et al , 2006a) and InGaN MQW green (Cartwright et al, 2006) LEDs grown on the bulk AlN substrates and blue and UV LED on the bulk GaN substrates (Cao et al, 2004;Cao et al , 2004a;Du, Lu, Chen, Xiu, Zhang & Zheng, 2010) as well as cyan and green LEDs grown on a-plane (Detchprohm et al, 2008) and m-plane (Detchprohm et al, 2010) GaN bulk substrates prove the superiority of the native substrates, e.g., the luminescence intensity of the quantum well grown on bulk AlN was higher that that of the quantum well grown on SiC by a factor of 28, the noticeable improvement over LEDs grown on sapphire in device impedance and thermal characteristics (Ren et al , 2007a), the reduction in current-voltage differential resistance and in turn-on voltage (Paskova et al, 2010). The emission spectrum of AlGaN-based UV-LEDs on a bulk AlN substrate under the high current injection is much more stable than that of LEDs fabricated on the conventional substrate (Nishida et al, 2004a;.…”
Section: Epitaxial Layers and Devices On Single-crystal Native Iii-nimentioning
confidence: 89%
“…The comparison of photoluminescence of the GaN layers deposited on the Al face and on the N face of the single-crystal AlN substrate showed that in the former case photoluminescence is consistent with that of the homoepitaxial Ga-face GaN while in the latter an existance of the tail localized states was found (Tamulatis et al, 2003). The studies of deep-UV emission of AlGaN quantum wells (Gaska et al, 2002) as well as AlGaN UV (Nishida et al, 2004a;Ren et al, 2007;Xi et al , 2006a) and InGaN MQW green (Cartwright et al, 2006) LEDs grown on the bulk AlN substrates and blue and UV LED on the bulk GaN substrates (Cao et al, 2004;Cao et al , 2004a;Du, Lu, Chen, Xiu, Zhang & Zheng, 2010) as well as cyan and green LEDs grown on a-plane (Detchprohm et al, 2008) and m-plane (Detchprohm et al, 2010) GaN bulk substrates prove the superiority of the native substrates, e.g., the luminescence intensity of the quantum well grown on bulk AlN was higher that that of the quantum well grown on SiC by a factor of 28, the noticeable improvement over LEDs grown on sapphire in device impedance and thermal characteristics (Ren et al , 2007a), the reduction in current-voltage differential resistance and in turn-on voltage (Paskova et al, 2010). The emission spectrum of AlGaN-based UV-LEDs on a bulk AlN substrate under the high current injection is much more stable than that of LEDs fabricated on the conventional substrate (Nishida et al, 2004a;.…”
Section: Epitaxial Layers and Devices On Single-crystal Native Iii-nimentioning
confidence: 89%